2006
DOI: 10.1177/0883911506065100
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Porous Chitosan/Collagen Scaffolds for Periodontal Tissue Engineering

Abstract: The wide array of periodontal tissue engineering applications has demonstrated the need for appropriate biodegradable materials. Porous chitosan/collagen – a natural derivative composite – scaffolds could be a candidate. In this study, differently proportioned porous chitosan/collagen scaffolds were prepared by controlled freezing and lyophylization of corresponding composite solutions. The scaffolds were investigated via aperture, porosity, swelling behavior and cell-mediated contraction testing. The morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 23 publications
2
46
0
1
Order By: Relevance
“…Collagen samples were stirred at 4 °C, whereas, chitosan samples were stirred at ambient temperature. Followed by stirring, the samples were subjected to centrifugation in order to remove any unreacted molecules and a clear solution obtained upon centrifugation at 5,000 RPM for 10 minutes and was poured in Tarson (India) vial of an inner diameter of 4.5 cm and frozen at -4 °C for 2 hours, -20 °C for 12 hours and -80 °C for another 12 hours 19 . The frozen samples were lyophilized for 48 h at a vacuum of 7.5 militorr (1 Pa) and a condenser temperature of -70°C (PENQU CLASSIC PLUS, Lark, India).…”
Section: Fabrication Of Scaffoldsmentioning
confidence: 99%
“…Collagen samples were stirred at 4 °C, whereas, chitosan samples were stirred at ambient temperature. Followed by stirring, the samples were subjected to centrifugation in order to remove any unreacted molecules and a clear solution obtained upon centrifugation at 5,000 RPM for 10 minutes and was poured in Tarson (India) vial of an inner diameter of 4.5 cm and frozen at -4 °C for 2 hours, -20 °C for 12 hours and -80 °C for another 12 hours 19 . The frozen samples were lyophilized for 48 h at a vacuum of 7.5 militorr (1 Pa) and a condenser temperature of -70°C (PENQU CLASSIC PLUS, Lark, India).…”
Section: Fabrication Of Scaffoldsmentioning
confidence: 99%
“…This property of the collagen is mainly due to the hydrophilic group associated with the collagen molecule through hydrogen bonding. This significant feature of the prepared 3D collagen was revealed not only by the enhanced absorption of exudates but also by the support provided by the permeation of oxygen at the wound site [18,19].…”
Section: Figure 3 Cone-beam Ct Images Of the 3d Col-spg At Different mentioning
confidence: 98%
“…However, fibrin could not be used alone on fabricating robust cellular scaffolds due to low mechanical properties [26]. Additionally, collagen is of particular interest, as it is a naturally derived material, biodegradable and biocompatible [27,28], and has been investigated for numerous applications as well, such as in vascular [29], skin [30], ligament [31], and bone [32] tissue engineering. Applications of collagen in bone tissue regeneration showed that it acts as a bioactive component supporting cell attachment, proliferation and initiating osteogenic differentiation [14].…”
Section: Introductionmentioning
confidence: 99%